Influence of reduction temperature on Ni particle size and catalytic performance of Ni/Mg(Al)O catalyst for CO2 reforming of CH4. (24th January 2020) - Zhan, Yingying; Song, Kai; Shi, Zemin; Wan, Chunsheng; Pan, Jinhua; Li, Dalin; Au, Chaktong; Jiang, Lilong
Abstract: Hydrotalcite-derived Ni/Mg(Al)O is promising for CH4 –CO2 reforming. However, the catalysts reported so far suffer from sever coking at low temperatures. In this work, we demonstrate that a significant improvement of coke-resistance of Ni/Mg(Al)O can be achieved by fine tuning the Ni particle size through adjusting the reduction condition of catalyst. Ni particles having average size within 4.0–7.1 nm are in situ generated by reducing the catalyst at a selected temperature within 923–1073 K. Controllability of Ni particle size is related to the formation of Mg(Ni, Al)O solid solution upon hydrotalcite decomposition. It is found that the catalyst reduced at 973 K exhibits high activity, stability, and coke-resistance even at reaction temperature as low as 773 K. In contrast, the catalyst reduced at 923 K has low activity and deactivates due to Ni oxidation, while those reduced at 1023 and 1073 K suffer from sintering and severe coking. STEM and O2 -TPO reveal that coke deposition is directly proportional to the Ni particle size but becomes negligible at a size below 6.2 nm. It is evidenced that a critical size of about 6 nm is required to inhibit coking effectively. CO2 temperature-programmed surface reaction indicates that the deposited carbon on small Ni particles can be easily removed by the CO2 activated at the Ni–Mg(Al)O interfaces, accounting for the better resistance to coking. Graphical abstract: Image 1 Highlights: Ni particles with sizes of 4–7.3 nm are obtained by adjusting reduction temperature. The catalyst reduced at 973 K is active and coke-resistant at 773–873 K. A critical Ni particle size of about 6 nm is required to inhibit coking effectively. Surface carbon on small Ni particles can be easily removed by CO2 .